Analisis Normatif Penanganan Anak Sebagai Pelaku Penyalahgunaan Narkotika Dalam Upaya Penegakan Hukum Yang Berkeadilan - Henky Irawan; Selamet Saputra; Satria Pandu Pradhana; Muhammat Apriza (Consensus : Jurnal Ilmu Hukum, 2025)
This study normatively examines the handling of children involved in narcotics abuse within the framework of achieving equitable law enforcement in Indonesia. The issue represents a multidimensional problem requiring an integrated legal, social, and psychological approach. According to Law Number 11 of 2012 on the Juvenile Criminal Justice System and Law Number 35 of 2009 on Narcotics, children in conflict with the law are entitled to special treatment. Employing a normative juridical method, this research analyzes relevant legislation and legal doctrines. The findings indicate that the resolution of narcotics abuse cases involving children should prioritize restorative justice principles, emphasizing recovery and social reintegration rather than punishment. Strengthening coordination among law enforcement institutions and implementing humane rehabilitation programs are essential to realize fair and child-centered law enforcement.